2017
DOI: 10.1007/s10570-017-1405-8
|View full text |Cite
|
Sign up to set email alerts
|

Barrier and mechanical properties of plasticized and cross-linked nanocellulose coatings for paper packaging applications

Abstract: Barrier, mechanical and thermal properties of porous paper substrates dip-coated with nanocellulose (NC) were studied. Sorbitol plasticizer was used to improve the toughness, and citric acid crosslinker to improve the moisture stability of the coatings. In general, the addition of sorbitol increased the barrier properties, maximum strength and toughness as well as the thermal stability of the samples when compared to the non-modified NC coatings. The barrier properties significantly improved, especially for pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
43
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(52 citation statements)
references
References 32 publications
(63 reference statements)
2
43
0
Order By: Relevance
“…Optical and SEM images(Figures 4,5,8,9) of welded films suggested that surface texturing of welded films occurs, which may also affect their mechanical properties. Therefore, strength and barrier properties were measured.…”
mentioning
confidence: 99%
“…Optical and SEM images(Figures 4,5,8,9) of welded films suggested that surface texturing of welded films occurs, which may also affect their mechanical properties. Therefore, strength and barrier properties were measured.…”
mentioning
confidence: 99%
“…NC has a high aspect ratio (4-20 nm wide, 500-2000 nm in length) and also excellent film forming ability because of physical entanglement and hydrogen bonding between adjacent NC [1]. NC was reported to have prospective applications for bio-based materials to be used in food packaging, for instance, as reinforcement filler and plasticizer in edible films [2], as self-standing thin films for modified atmosphere packaging [3], or as a coating over paper packaging [4,5]. In particular, NC film has a good oxygen barrier property [6] which is important in food packaging considering prevention of lipid oxidation [7].…”
Section: Introductionmentioning
confidence: 99%
“…Biomass-derived materials have attracted attention owing to their abundant resources, renewability, and biodegradability (Jonoobi et al 2014;Khalil et al 2012;Oksman et al 2003). Nanocellulose materials, including cellulose nanofibers (CNFs) and cellulose nanocrystals (CNCs), that can be extracted from various types of biomass have attracted considerable interest owing to their specific physical and chemical properties (Geng et al 2018;Herrera et al 2017;Nissilä et al 2019). Recently, several studies on the preparation of highly porous nanocellulose-based aerogels using ice-templating have been reported, and some have shown interesting adsorption/absorption capabilities.…”
Section: Introductionmentioning
confidence: 99%